Epididymal epithelium propels early sexual transmission of Zika virus in the absence of interferon signaling - Pletnev, Alexander G.; Maximova, Olga A.; Liu, Guangping; Kenney, Heather; Nagata, Bianca M.; Zagorodnyaya, Tatiana; Moore, Ian; Chumakov, Konstantin; Tsetsarkin, Konstantin A. (Nature communications, 2021)
Recognition of Zika virus (ZIKV) sexual transmission (ST) among humans challenges our understanding of the maintenance of mosquito-borne viruses in nature. Here we dissected the relative contributions of the components of male reproductive system (MRS) during early male-to-female ZIKV transmission by utilizing mice with altered antiviral responses, in which ZIKV is provided an equal opportunity to be seeded in the MRS tissues. Using microRNA-targeted ZIKV clones engineered to abolish viral infectivity to different parts of the MRS or a library of ZIKV genomes with unique molecular identifiers, we pinpoint epithelial cells of the epididymis (rather than cells of the testis, vas deferens, prostate, or seminal vesicles) as a most likely source of the sexually transmitted ZIKV genomes during the early (most productive) phase of ZIKV shedding into the semen. Incorporation of this mechanistic knowledge into the development of a live-attenuated ZIKV vaccine restricts its ST potential. Zika virus can be sexually transmitted. Here, Pletnev et al. show in an immunocompromised mouse model that the epithelial cells of the epididymis, rather than cells of the testis, vas deferens, prostate, or seminal vesicles, are the most likely source of male-to-female sexually transmitted ZIKV genomes.